The citation and link analysis among hadith bulugh al-maram min adillah al-ahkam by Imam Ibn Hajr Al-'Asqalani - Muhammad Alif bin Ismail (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
This research focused on citation and link analysis among hadith in Bulugh al-maram min adillah al-ahkam by Imam Ibn Hajr al-'Asqalani. The citation and link counts involved 101 of 1399 hadith which on topics of introduction to marriage (Nikah), wedding gift (Maskahwin), reception (Walimah), divorce (Thalaq), menstrual cycle ('Iddah dan Ihdad) and livelihood (Nafkah). The purpose of this research is to identify the pattern of citation and link within the contribution made by narrators (Rawi) among the Imam Sab'ah, co-narrators (Mukhrij) among the Successors of the Followers of Prophet Muhammad P.B.U.H and Rijal (NoName transmitter). It is also intended to recognize the number of hadith cited by the transmitters. This research used Protégé version Beta 4.2 to analyse and illustrate the link graphically. Name of relationships in Object Property Hierarchy is also considered. The relationship among the transmitters and hadith is described through Arc Types and Object Property Hierarchy. Based on the results, Muslim (42 of 160 citations) and Ibn Hibban (13 of 53 citations) dominated the citation and link counts. On the contrary, less domination among transmitters is Tirmidzi (17 of 160 citations) and other transmitters with one citation, for instance, Abu 'Awamah, Abu Hatim, Abu 'Isa at-Tirmidzi, Abu Ya'ala, Al-Bazzar, Ibn 'Adiy, Ibn Khuzaimah, Ibnul Madini, Jama'ah and Zuhaily. Additionally, the most popular hadith cited by transmitters is introduction to marriage (Nikah), which is 76 of 172 citations from narrators (Rawi) and 20 of 54 from co-narrators (Mukhrij). Considering these findings, the necessary patterns of hadith transmitters revealed the contribution and relationship among them are among the people of Hadith.